Optimizing culture conditions of human umbilical cord mesenchymal stem cells (hUC-MSCs) by adjusting the volume of xeno-free supplement serum - Sam, Nguyen Thi; Huyen, Nguyen Thi; Phuong Anh, Nguyen Thi; The Dan, Pham; Thuy Ngan, Nguyen Thi; Hoang Ha, Chu; Trung Nam, Nguyen (Vietnam Journal of Biotechnology, 2023)
Mesenchymal stem cells (MSCs) have become an effective tool for treating immune-related diseases due to their multilineage potential and immunomodulatory capabilities. However, a high cell dose is frequently essential for stem cell infusion in clinical practice. Therefore, it is necessary to produce sufficient quantities of MSCs while ensuring cell quality for clinical application in humans. To be able to use stem cells in patients requires a more rigorous captive procedure than using a xeno-free medium that does not contain substances derived from the hypothetical allergenic regime. Therefore, current cell culture procedures substitute xeno-free culture media with added supplement serum for the traditional DMEM media with bovine fetal serum (FBS). This switch increased the production cost immensely and made it difficult to produce MSCs on an industrial scale. In this study, we optimized the condition of MSCs’ cultures by adjusting the amount of the supplement serum usage to reduce production costs for industrial manufacturing. This is the first study to claim that reducing the amount of xeno-free supplement serum had no effect on the quality of hUC-MSCs isolated from Vietnamese children’s umbilical cords.